S-Thyroid Computer-Aided Diagnosis Ultrasound System of Thyroid Nodules: Correlation Between Transverse and Longitudinal Planes - Yang, Keen; Chen, Jing; Wu, Huaiyu; Tian, Hongtian; Ye, Xiuqin; Xu, Jinfeng; Luo, Xunpeng; Dong, Fajin (Frontiers in Physiology, 2022)
Introductions We compare the differences in the diagnostic results of S-thyroid, a computer aided diagnosis (CAD) software, based on two mutually perpendicular planes. Methods 149 thyroid nodules confirmed by surgical pathology were enrolled in our study. CAD in our study was based on ACR TI-RADS lexicon. T test, rank sum test and Chi-square test were used. Interclass correlation coefficient and Cohen's kappa were used to explore the correlation between CAD features. Receiver operating characteristic was plotted for different combinations of CAD features. Results The patient’s age, transverse diameter, longitudinal diameter, shape, margin, echogenicity, echogenic foci, composition, TI-RADS classification and risk probability of nodules in the transverse and longitudinal planes were related to thyroid cancer(P<0.05). The AUC (95%CI) of TI-RADS classification in the transverse plane of CAD is better than that of the longitudinal plane [0.90(0.84-0.95) vs 0.83(0.77-0.90), P=0.04]. The AUC (95%CI) of risk probability of nodules in the transverse planes shows no difference in that in the longitudinal plane statistically [0.90 (0.85-0.95) vs 0.88 (0.82-0.94), P=0.52]. The AUC (95%CI), specificity, sensitivity and accuracy of [TI-RADS classification (transverse plane) + TI-RADS classification (longitudinal plane) + risk (transverse plane) + risk (longitudinal plane)] is 0.93(0.89-0.97), 86.15%, 90.48%, 88.59% respectively. Conclusions The diagnosis of thyroid cancer in the CAD transverse plane was superior to the CAD longitudinal plane when using the TI-RADS classification, but there was no difference in the diagnosis between the two planes when using risk. However, the combination of CAD transverse and longitudinal planes had the best diagnostic ability.